2009
DOI: 10.1002/adma.200802420
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Properties at Gold/Conjugated‐Polyelectrolyte Interfaces

Abstract: The chemical structures and electronic structures at conjugated polyelectrolyte/Au interfaces demonstrate that conjugated polyelectrolytes with identical backbones but different pendant charges and charge‐compensating ions exhibit different electronic properties. This finding shows that counterions and backbone charges enable control of the electronic and chemical nature of critical device interfaces.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
139
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 143 publications
(146 citation statements)
references
References 40 publications
7
139
0
Order By: Relevance
“…In a series of earlier reports it has been shown that the transient response of mobile ion possessing CPE-based PLEDs is strongly dependent on the ion size and environment (including neighboring functional groups). 9,12,13,19,29,31 The striking difference here between F8im-Br and F8imBT-Br which possess the same mobile bromide ion and imidazolium side chain tethered ionic groups represents a significant deviation from typical behavior. The low electron injection barrier for F8imBT-Br in contact with the Al electrode might also contribute to the fast transient response observed by minimizing the field dropped across the EIL.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…In a series of earlier reports it has been shown that the transient response of mobile ion possessing CPE-based PLEDs is strongly dependent on the ion size and environment (including neighboring functional groups). 9,12,13,19,29,31 The striking difference here between F8im-Br and F8imBT-Br which possess the same mobile bromide ion and imidazolium side chain tethered ionic groups represents a significant deviation from typical behavior. The low electron injection barrier for F8imBT-Br in contact with the Al electrode might also contribute to the fast transient response observed by minimizing the field dropped across the EIL.…”
Section: Resultsmentioning
confidence: 92%
“…[4][5][6][7][8][9][10] It was reported that the charged nature of CPEs has the ability to enhance polymer light-emitting diode (PLED) efficiencies as a consequence of reduction in the energy barrier for electron injection from high work function metals, much in the same way that charge trapping can, but with greater control and no requirement for pre-stressing. 11 This is understood mainly due to the formation of permanent dipoles at the CPE/metal interface 12,13 as also achieved with dipolar self-assembled monolayers (SAMs), but without their need for specific interface chemistry. 14 CPEs can also be used to improve the device performance of organic solar cells.…”
Section: Introductionmentioning
confidence: 99%
“…The charged CPE electron transport layers (ETLs) are believed to lower the charge injection barrier between the high work function electrode and the active layer by creating a permanent dipole between the metal and the CPE, in addition to a migration of charged ions into the film. [11][12][13][14] Although enhanced efficiency in PLEDs has been demonstrated using CPEs, [8,15] these polymers require complicated synthesis routes. The most effective polymers have used a hole-transporting polyfluorene backbone, which could hinder their hole-blocking properties.…”
Section: Introductionmentioning
confidence: 99%
“…Recently a polymer/oxide interface was thoroughly examined by use of multiple samples with varying thickness polymer films under the assumption that the substrate surfaces were the same for all samples. 74 Schlaf and coworkers have also performed in situ deposition of polymers via electrospray deposition to evaluate the interfacial energy alignment. 77 HAXPES is well suited to the study of a polymer/substrate interface since a single sample can be probed at varying depths.…”
Section: Haxpes Of Protected Ito Interfaces With P3htmentioning
confidence: 99%
“…7, 14, [72][73][74][75][76] Interfacial modifications and/or the presence of adventitious species have been shown to dramatically affect performance of organic electronic devices. 4,5,32 In organic photovoltaics (OPVs) and organic light emitting diodes (OLEDs) charge injection barriers can be present due to energy level offsets, and also due to the presence of undesirable chemical species at the interface.…”
Section: Haxpes Of Protected Ito Interfaces With P3htmentioning
confidence: 99%